Urban Repair: Designing with/for More-Than-Human Life. Booklet - Bravo Rabaneda, Aitana; Carmona Calero, María; García Castro, María; Cimadomo, Guido; España-Naveira, Paloma (My University, 2025)
Booklet with context, information, program and additional resources for the 2025 SArPe International Summer School.
Booklet with context, information, program and additional resources for the 2025 SArPe International Summer School.
Keywords: Zonas verdes - Málaga; Política urbana - Aspectos sociales; Bosque Urbano Málaga; BUM; Urban forest; Summerschool; Urban repair